Gaya Bahasa dalam Program Budi Dalton Ngomongkeun Batur (Ngobat) di Youtube Channel - Sonjaya, Soni (Media Nusantara, 2021)
Viewers and fans of the Budi Dalton Ngobat program cross cultural boundaries and linguistic diversity, but Budi Dalton chooses his own style of language that reflects his Sundanese dialect or accent. The communication style used by Budi Dalton as a presenter aims to make the communication message digestible by the audience. Inequality in the perception of the village towards a dialect or accent in Indonesia still occurs due to the role of the media which tends to favor certain dialects or accents. Submission of important messages even containing high information value can be conveyed in their respective language styles, depending on institutional agreements and individuals involved in communication.